2022
DOI: 10.1200/jco.2022.40.4_suppl.238
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled phase III trial comparing two chemotherapy regimen and chemoradiotherapy regimen as neoadjuvant treatment for locally advanced esophageal cancer, JCOG1109 NExT study.

Abstract: 238 Background: Neoadjuvant treatment is the standard care for locally advanced esophageal squamous cell cancer (ESCC). JCOG1109 (UMIN000009482) compared the doublet and triplet of chemotherapy and chemoradiotherapy as neoadjuvant treatment. Methods: Eligible patients (pts) with ESCC of clinical stage IB, II, III (excluding T4) (UICC 7th) from 44 institutions were randomized 1:1:1 to neoadjuvant CF (cisplatin 80 mg/m2 on day1 plus 5-FU 800 mg/m2 on days 1-5 Q3W/2course), DCF (docetaxel 70 mg/m2 on day 1, cisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
130
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 166 publications
(139 citation statements)
references
References 0 publications
6
130
2
1
Order By: Relevance
“…Although this study did not include EP, additional immune-check point inhibitor is of importance to evaluate for EP. Another study is new NAC triplet regimen from JCOG ( 119 ). JCOG 1109 shows triplet regimen is superior efficacy compared to doublet regimen.…”
Section: Stage Ii/iii (Non-t4)mentioning
confidence: 99%
“…Although this study did not include EP, additional immune-check point inhibitor is of importance to evaluate for EP. Another study is new NAC triplet regimen from JCOG ( 119 ). JCOG 1109 shows triplet regimen is superior efficacy compared to doublet regimen.…”
Section: Stage Ii/iii (Non-t4)mentioning
confidence: 99%
“…Based on the findings above, neoCRT plus surgery has become a recommended option for locally advanced ESCC. However, the improved pCR rate in neoCRT did not provide a more significant long-term survival advantage than in neoCT ( 18 , 19 ). In addition, the clinical application of neoCRT is restricted due to the toxicity of CRT and the superimposed toxicity of chemotherapy and radiotherapy.…”
Section: Discussionmentioning
confidence: 88%
“…Therefore, NAC with CF might be insufficient for these patients. Recently, the JCOG1109 trial showed the superiority of triplet NAC (docetaxel plus CF) over CF in terms of survival [15]. Also, in the CheckMate 577 trial, adjuvant immune checkpoint inhibitor (ICI) offered a better prognosis in ESCC patients who underwent NACRT followed by curative esophagectomy [16].…”
Section: Discussionmentioning
confidence: 99%